The influence of leadership behaviour on organisational citizenship behaviour in self-managed work teams in Malaysia - Omar, Zoharah; Zainal, Arifin; Omar, Fatimah; Khairudin, Rozainee (OpenJournals Publishing, 2009)
his study examined the influence of transformational-transactional leadership behaviour on organisational citizenship behaviour in self-managed work teams and the augmenting effect of transformational-transactional leadership behaviour. This cross-sectional correlation study was conducted on 93 self-managed work teams in a multinational manufacturing company. Data were collected through group face-to-face administration by the researcher and statistically analysed through Pearson correlation, partial correlation and multiple regressions. Results showed that both transactional and transformational leadership behaviour have a positive influence on organisational citizenship behaviour among team members. Transformational leadership behaviour, however, has a greater influence on organisational citizenship behaviour compared to transactional leadership behaviour. The results also conf rmed the augmenting effect of transformational leadership behaviour on the relationship between transactional leadership behaviour and organisational citizenship behaviour.